In situ TEM investigation of electron beam-induced ultrafast chemical lithiation for charging. Issue 2 (11th December 2019) - Huang, Guan-Min; Huang, Chun-Wei; Kumar, Nagesh; Huang, Chih-Yang; Tseng, Tseung-Yuen; Wu, Wen-Wei
Abstract : An innovative strategy for harvesting energy harvesting usingin anthe NiFe2 O4 /CNT nanocomposite as an electrode material NiFe2 O4 /CNTs is proposed in this study. Abstract : The enhancement of operational life and charging speed have been considered to be two of the major factors that will influence the development of energy storage devices in the future. Here, we utilized an electron beam (e-beam) to retrieve Li metal from LiF, the degradation product of LiPF6, and trigger the further lithiation of NiFe2 O4 /carbon nanotubes (CNTs) to relieve the degradation of the electrolyte and achieve ultrafast lithiation. Accordingly, in situ transmission electron microscopy ( in situ TEM) was used to investigate the comprehensive mechanism of the whole process. The e-beam acting on the degradation product, i.e., LiF clusters, led to the generation of Li flakes, which served as the source for the subsequent lithiation. Then, with these Li flakes, the chemical lithiation of the NiFe2 O4 /CNTs was triggered, resulting in phase transformation to Ni and Fe nanograins. Compared to "electrochemical" lithiation, ultrahigh reaction speed and the ability to charge without a directly applied potential in the "chemical" lithiation are expected to extend lithiation to more diverse applications. As a result of this investigation, we have provided a new strategy for designing novel energy storage devices for the energy-harvesting field.